Economic And Economic-Statistical Designs Of Variable Sample Size And Sampling Interval Coefficient Of Variation Chart And Development Of Variable Sample Size Multivariate Coefficient Of Variation Chart For Short Runs - Chew, Yiying (2023)
Control charts are one of the most useful statistical process control tools that have been adopted for process monitoring in numerous fields. Traditional control charts are ineffective in process monitoring when the process being monitored does not have the process mean and variance that are independent of one another. Under such a circumstance, the coefficient of variation (CV) is used in process monitoring, where the ratio of the standard deviation to the mean is monitored. The variable sample size and sampling interval CV (VSSI CV) chart was shown to be more effective than the Shewhart CV (SH CV) chart in the literature but only in terms of the statistical performance. Thus, the first objective of this thesis is to investigate the economic and the economic-statistical performance of the VSSI CV chart. By minimizing the cost via the economic and economic-statistical designs, the VSSI CV chart can be implemented more economically. The economic and economical-statistical performance of the VSSI CV chart is studied using numerical examples, where comparisons with the SH CV chart are made. The results show that the VSSI CV chart outperforms the SH CV chart, in terms of both economic and economic-statistical performance. A study on the misspecification of the shift size is also conducted to study the effect of wrongly specifying the shift size on the optimal cost.